Oral Health Behaviour and Predictors of Oral Health Behaviour Among Patients With Diabetes in the Republic of Mauritius - Nesha Paurobally; Estie Kruger; Marc Tennant (Elsevier, 2022)
Objectives: To investigate the oral care habits and assess the determinants of oral care behaviour among people with diabetes in the Republic of Mauritius. Methods: The present study draws on data collected from 589 dentate persons with diabetes by means of a close-ended questionnaire. Multivariate logistic regression analyses were used to estimate the association of different demographic and clinical factors with recommended dental hygiene practices. Results: The majority of the participants brushed at least twice daily (84.2%), never flossed (88.6%), attended dental clinics on need only (87.1%), and did not monitor their blood glucose levels regularly (69.9%). Neither awareness about the increased risk of periodontal disease and xerostomia nor receiving advice from diabetes care providers was found to be associated with good oral hygiene or increased service utilisation. The experience of oral diseases did not encourage recommended oral health practice, with participants without experience with periodontal disease being 3 times more likely to floss (odds ratio [OR], 2.9; P = .045). Regular dental visits were strongly associated with self-reported type 1 diabetes (OR, 7.8; P = .025). Participants from urban areas were more than twice as likely to visit their dental care provider at least once annually (OR, 2.3; P = .006). Regular dental attendance (OR, 3.7; P = .011) and flossing (OR, 4.5; P = .012) were strongly associated with one another. Conclusion: There is widespread noncompliance with regular flossing and dental service utilisation. Our findings highlight the need for an emphasis on preventive care through the provision of integrated medical and dental interventions to high-risk individuals suffering from both diabetes and chronic periodontitis.